Dinámica de la descomposición de la hojarasca fina en diferentes plantaciones: Ormosia coccinea (Aubl.) Jackson "huayruro", Cedrelinga cateniformis (Ducke) Ducke "tornillo" y bosque secundario de tierra firme, Iquitos - Perú, 2016 - Gonzales Grandez, Patricia Giovanna (2021)
The objective of this study was to evaluate the variation in the dynamics of fine litter decomposition in plantations of Ormosia coccinea (Aubl.) Jackson “Huayruro”, Cedrelinga catenaeformis (Ducke) Ducke “Tornillo” and Secondary Forest of Tierra Firme, in the Center for Forestry Research and Teaching - UNAP. Plots of 25 x 50 m were delimited, placing 30 plastic mesh bags, in plantations and secondary forests, methodology proposed by Bocock(1) and withdrawn at 30, 60, 120, 270 and 365 days. In the physical dynamics, the humidity increased progressively throughout the decomposition process, the residual weight was intense and with a higher value at the beginning of the decomposition, the annual rate of decomposition of the fine litter in all the study areas was greater than 2.5 k year -1, being the secondary forest the area with the highest rate of decomposition, with 2.72 k year -1, average life index of 134 days. From 30 to 120 days the highest values of the decomposition rate were recorded in all the study areas. In structural dynamics, the percentage of brittle and / or discolored leaves, skeletonized, and root colonization increased gradually from the beginning of the study to 365 days. The biological dynamics reported the phylum Arthropods as very diverse and the orders with the highest number of families Mites, Coleoptera, Diptera and Hemiptera. The mites of the arachnid group reported the highest number of identified families. The colonization of soil macroinvertebrates started from 30 days. Finally, the decomposition rate and the richness of soil macroinvertebrates in secondary forests are strongly and directly correlated, on the contrary, the decomposition time was strongly and inversely correlated with abundance.